Active compound, antioxidant, antiproliferative and effect on STZ induced zebrafish of various crude extracts from Boletus qriseipurpureus - Sutha Muniandy,; Fauzi Daud,; Sahidan Senafi,; Mahanem Mat Noor,; Malina Kumaran,; Andi Norafiqah Andik Mohd Alwi,; Ayumawarni Yusni Yeng Jee Long,; Rahimah Mohamad Zuki,; Janet Salomi Isac,; Subhashini Krishnan,; Deeviya Gobalan,; Lim, Yi Chieh; et al. (Malaysian Society of Applied Biology, 2016)
Boletus qriseipurpureus (gelam mushroom) is a mushroom used by locals in Tok Bali, Kelantan, Malaysia to treat diabetes, cervical cancer and breast cancer. The active compounds in B. qriseipurpureus remain unidentified. Therefore, in this study, we investigated the potential medicinal properties of B. qriseipurpureus extracts (hot water, cold water and methanol extracts) by conducting preliminary phytochemical screening, in vitro antioxidant, in vitro antiproliferative and in vivo antidiabetic test. Biochemical assays were performed to detect the presence of alkaloids, anthraquinones, flavonoids, reducing sugars, saponins, steroids and tannins in B. qriseipurpureus extracts. 1,1-diphenyl-2-picrylhydrazyl (DPPH) was used to evaluate the antioxidant capacity of B. qriseipurpureus extracts, while MTT cell proliferation assay (3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide) was used to investigate the extracts antiproliferative activity. The effects of B. qriseipurpureus extracts on streptozotocin (STZ) induced zebrafish were examined at the concentration of 45 mg/mL, 90 mg/mL and 135 mg/mL. The effect of extracts were measured by the regenerative growth rate of the amputated caudal fin for fourteen days post transection. Screening of the mushroom extracts for active compounds revealed the presence of alkaloids, flavonoids, saponins and tannins in all test extracts. Reducing sugars and anthraquinones are only detected in hot water and cold water of B. qriseipurpureus extracts. The half maximal inhibitory concentration (IC50) of DPPH by hot water, cold water and methanol extract of B. qriseipurpureus are 1.79 mg/mL, 1.97 mg/mL and 3.98 mg/mL respectively. The MTT assay indicated that all extracts exhibited significant antiproliferative effects on MCF-7 cell line after 72 hours with IC50 of 7.7 mg/mL for hot water extract, 8.2 mg/ mL for cold water extract and 16.1 mg/mL for methanol extract but do not display any significant cytotoxic effect. The STZ induced zebrafish treated with 135 mg/mL of hot water B. qriseipurpureus extract for 14 days showed the highest regeneration growth rate of caudal fin (5.04 ± 0.43%) compared to fish treated with metformin (5.72 ± 0.64 %). In this study, we showed the potential of hot water B. qriseipurpureus extracts as a potent therapeutic agent for diabetes and as an alternative natural source of antioxidant.